Analysis of Factors Affecting Customer Decisions in Choosing Savings Products at PT. Bank Syariah Mandiri Bengkulu Branch - Ade Herlena; Neri Susanti; Siti Hanila (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2021)
The purpose of this study is to determine the most dominant factors that influence customer decisions in choosing savings products at PT. Bank Syariah Mandiri Bengkulu Branch, as for these factors are: (1) Social Factors, (2) Cultural Factors, (3) Factors Personal, (4) Psychological Factors. Theory related to the title Analysis of Factors Influencing Customer Decisions in Choosing Savings Products at PT Bank Syariah Mandiri Bengkulu Branch was motivated by intense competition between financial institutions, where Bank Syariah Mandiri is focused on goods and financial services companies that have established since October 25, 1999 until now, where the Sharia Bank itself operates in accordance with the Qur'an and Hadith and the necessity for a Sharia Supervisory Board (DPS). As for the number of respondents in this study as many as 50 people, and the sampling technique used is accidental sampling. The data source uses primary data by filling out questionnaires, and distributing questionnaires to respondents. The method in this study uses a rating scale.The conclusion of this study is that all factors influence customer decisions, but there are the most dominant factors, namely Social Factors and Personal Factors. After conducting research the results of the calculation of the average value of social factors are 204 and 197 the average value of personal factors.